Integrated nutrient management on soil fertility, growth and yield of tomato - Islam, MR; Chowdhury, MAH; Saha, BK; Hasan, MM (Journal of the Bangladesh Agricultural University, 2014)
To evaluate the effects of integrated nutrient management on growth and yield of BARI tomato-14 and soil fertility, a pot experiment was conducted in the net house of the department of Agricultural Chemistry of Bangladesh Agricultural University, Mymensingh during the period from October 2011 to April 2012. The experiment was laid out in a completely randomized design with 11 treatments and 3 replications. Treatments were control, RDCF100, 75% RDCF, 50% RDCF, 75% RDCF + PM2 t /ha, 75% RDCF + RS3 t /ha, 75% RDCF + PHRD, 50% RDCF + PM3 t /ha, 50% RDCF + RS5 t /ha, 50% RDCF + PHRD, PM3 t /ha + RS5 t /ha + PHRD. Among the treatments applied in combination of PM2 t /ha+ 75% of RDCF excelled in growth trends of morphological characters like plant height, number of branches plant- 1, number of leaves plant-1; available soil P and S. But sole application of RDCF100 recorded higher values for almost all morphological characters namely number of branches plant-1, number of leaves plant-1, fruit diameter, fruit weight plant-1 and yield of tomato following the same trend as seen in combined application of CF and PM. Among the plant hormone applied in combination, RDCF75% + PHRD showed the highest plant height. The more number of leaves plant-1, number of branches plant-1, yield and yield parameters as compared to other treatments were also significantly influenced by application of PH. Combined application of 50% of RDCF+RS5 t /ha increased exchangeable soil K. PM3 t /ha+ RS5 t /ha+ PHRD conserved more organic carbon and total soil N. Results showed that the integrated use of PM, RS along with CF increased the availability of nutrients throughout the growth period by maintaining the long term productivity for sustainable production of tomato. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18204 J. Bangladesh Agril. Univ. 11(1): 33-40, 2013